Predicting Factors that Influence Consumer Purchase Intention for Online Shopping When Seller Live Streaming on Social Media - Syafira Ahsanti; Usep Suhud; Rahmi (LPPM Universitas Negeri Jakarta, 2022)
The purpose of this study was to example the effect of shopping orientation, sales promotion and trust on purchase intention to shop online when seller was live streaming on social media. The data collection method used a survey method in the form of a questionnaire via google form. Respondents in this study were consumers of social media users (17-40 years old) who lived in DKI Jakarta, liked to shop online through social media and found 200 respondents. The data analysis technique used AMOS version 26 and SPSS version 26 to process and analyse data from the research result. The result of the study can show that the variables of shopping orientation, online trust have a positive and significant effect on purchase intention. The variable of shopping orientation, sales promotion has a positive and significant effect on online trust. The sales promotion variable does not have any effect on the purchase intention variable.